Introducing a family intervention to elderly with first episode psychosis. (26th March 2018) - Saarela, Tuula; Johansson, Monica; Louhija, Ullamarja; Appelberg, Björn; Juva, Kati
Abstract : Schizophrenia guidelines list family interventions as an efficient means in reducing relapses. Interventions aim to help families cope with their relative's problems more effectively, provide support and education, and reduce levels of distress and improve the family communication (see deHaan et al., 2002 ).